Morphological and biochemical characterization of Moroccan Opuntia dillenii fruit: Natural source of bioactive compounds - Sofia ZAZOULI; Ghizlane Kabiri (Vitae)
Background: The fruit of Opuntia dillenii, commonly known as prickly pear, is widely consumed for its nutritional and medicinal benefits, such as anti-inflammatory and antioxidant properties. It plays a significant role in local diets and traditional medicine, contributing to economic value. However, research on its phytochemical composition and health benefits is limited, highlighting the need for further investigation. Objectives: The current study assessed morphological traits, biochemical composition, and antioxidant activity using the 2,2-diphényl-1-picrylhydrazyl (DPPH) assay. Methods:The morphological traits, biochemical parameters, and antioxidant content of the Moroccan O. dillenii fruit fractions, namely peel, juicy pulp, and seeds, were investigated. Results: The coefficient of variation of the morphological traits oscillated between 16.03 % for fruit weight and 51.83 % for seed weight, indicating a broad level of morphological variability. The total phenolic content of fruit fractions ranged from 202 to 56 g EAG/ 100 g extract, while the total flavonoids varied from 185 to 11 mg EC/100g extract. In addition, the total levels of betacyanins, betaxanthins, and condensed tannins ranged from 6.1 to 335 mg/L, 4.7 to 123 mg/L, and 12 to 8.3 mg/100g, respectively. As for ascorbic acid, it was concentrated in the juicy pulp at 580 mg/100 g, while it was absent in the seeds fraction. The phenolic compounds, flavonoids, and betalain contents were significantly correlated with antioxidant activities, whereas total ascorbic acid and condensed tannins were weakly correlated. Conclusion: These findings suggest that O. dillenii fruits may be a potential source of natural antioxidants for both food applications and medicinal functions.